Konstruksi Makna Melalui Majāz Mursal dalam Al-Qur’an: Analisis Kritis Retorika Ilahi pada QS. Al-‘Ankabut Ayat 41 - Ahmad Aqiel Azkiya’; Rizki Maulana Putra; Muhammad Bayu Fitriansyah; Muhamad Khabib Imdad; Edi Komarudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2025)
This study investigates the use of majāz mursal in QS. al-‘Ankabūt [29]: 41 as a rhetorical strategy in the construction of Qur’anic meaning. The verse presents a parable comparing those who associate partners with Allah to a spider building its house, where the spider’s web symbolically represents a fragile and unreliable system of dependence. Employing a qualitative-descriptive approach with rhetorical and semantic analysis, this research explores the form of majāz mursal maḥalliyyah in the verse's linguistic structure and the symbolic function of the spider’s house in conveying theological critique of polytheism. The primary data, drawn from the Qur’anic text, is analyzed using classical balaghah theory and contemporary Qur’anic rhetorical frameworks. The findings reveal that majāz mursal in this verse not only enhances linguistic aesthetics but also serves as a central instrument in communicating implicit existential and spiritual messages. The metaphor of the spider’s house effectively evokes the reader’s awareness of the frailty of all forms of reliance other than on Allah. This study affirms that figurative language in the Qur’an operates as a powerful vehicle of divine communication rather than merely a literary embellishment.